Epidemiology of musculoskeletal injuries and injury mechanism in Iranian elite veteran athletes - Rashid, H. F.; Daneshmandi, H.; Norasteh, A.; Roushan, Z. A. (Medicina dello Sport, 2023)
BACKGROUND: In recent years, the study of the epidemiology of injuries of athletes during their sports career has been accelerated by researchers and responsible national and international institutions. Repetitive and continuous patterns and types of injuries with mechanisms of micro trauma and overuse and macro trauma and impact are some of the most important reasons that can leave an unpleasant legacy from sports during retirement for veteran athletes. METHODS: A researcher-made questionnaire was used to record the musculoskeletal injuries of retired elite athletes. Overall, 276 athletes in three sports - volleyball (N.=86), soccer (N.=107) and basketball (N.=80) - contributed in this study. In this questionnaire, three important and severe injuries during sports of veterans were selected based on priority by the athlete himself. Injury registration was done according to the injury location, damaged structure and mechanism of injury. RESULTS: Kruskal-Wallis Test to check the amount of injury per 1000 hours of training among the studied groups showed not significant difference between groups (P=0.202). The most common injury location in all three groups was the foot and leg, this rate in volleyball athletes was 40.4%, in soccer athletes was 45.8%, and in basketball athletes was 35%. The results showed a significant difference in the most common injury location between the three studied groups (P=0.008). Ligament injuries were the most common type of injury in athletes. The results showed a significant difference between the 3 studied groups (P=0.008). Results showed a significant difference in the mechanism of injury between the three studied groups (P=0.008). CONCLUSIONS: Presenting the profile of musculoskeletal injuries of veteran athletes with the aim of explaining preventive strategies to reduce and eliminate injuries needs more studies. Especially since the present study was conducted during the corona pandemic period. The necessity of systematic screening and completing the rehabilitation process of athletes at the right time will reduce the risk of permanent and chronic injuries and will increase his physical, mental and social health during retirement.